IRON REMOVAL PROCESS FROM NICKEL PREGNANT LEACH SOLUTION USING SODIUM HYDROXIDE - Zunaidi, Mochamad Afriansyah; Setiawan, Iwan; Oediyani, Soesaptri; Irawan, Januar; Rhamdani, Ahmad Rizky; Syahid, Adi Noer (Metalurgi, 2022)
Indonesia is a country that has abundant mineral resources, including nickel resources in laterite ore. Nickel demand has risen significantly because of the need for nickel precursors for battery production. Nickel laterite can be processed via the hydrometallurgical route to obtain nickel precursor by leaching the laterite ore with an acid solution to produce a nickel-rich solution or Pregnant Leach Solutions (PLS). This nickel-rich solution is then processed by precipitation with a base solution to make its hydroxides known as Mixed Hydroxides Precipitate (MHP). MHP is the main product that contains nickel and cobalt for making the material for a lithium battery. PLS usually contain iron impurity, which also dissolves when the ore is leached. Therefore, the iron needs to be separated to make high-purity MHP. To solve this problem, synthetic PLS contained nickel, cobalt, and iron, and their concentration was simulated to match the general PLS composition. From the experiment, it was observed that iron could be precipitated at two stages at solution pH of 3 and 3.5 using 2.5 M NaOH solution. After that, nickel and cobalt can be precipitated at higher pH. To study the effect of pH and temperature on the yield of nickel and cobalt precipitation, precipitation at pH of 7, 8, and 9; and temperature of 70, 80, and 90 °C was conducted. The results show that the highest yield was obtained at a pH of 9 and temperature of 90 °C, with precipitation yield of nickel and cobalt at 99.03% and 98.78%, respectively.